Going High to Keep Body Mass Low: How Post-Exercise Exposure to a Simulated High Altitude Influences Energy Balance—A Proof-of-Concept Pilot Study - Peyton E. Allen; Akinola D. Akinwumi; Evan G. Kroeze; Paula Y. Leigh; Sahnet N. Ramirez; Gregory L. Smart; Tay M. Thomas; Hunter L. Paris (Obesities, 2024)
A healthy body mass contributes to a positive quality of life, and for overweight/obese individuals, weight loss of even modest proportions improves health-related outcomes. A novel approach to promoting body mass regulation is to pair exercise with high altitude, thereby upregulating metabolic processes and increasing caloric expenditure. As an added measure of body mass regulation, data suggest that high altitude stimulates the production of the appetite-suppressing hormone leptin. Issues arise, however, given that high altitude compromises aerobic exercise capacity. Whereas exercising at high altitude may compromise exercise intensity and duration, recovering at high altitude retains the integrity of exercise while still potentially conferring the benefits of the low oxygen environment on energy expenditure and energy intake. The purpose of this study was to perform a proof-of-concept pilot test on whether post-exercise exposure to a simulated high altitude influenced acute energy balance. Twelve healthy men and women ran for 30 min at a moderate intensity on two separate occasions. Following exercise, participants recovered for 30 min while breathing either sea level air or low oxygen air simulating high altitude (equivalent to 4500 m elevation). Blood samples and hunger ratings were collected pre-exercise and post-recovery. Heart rate was recorded throughout exercise and recovery and used to calculate caloric expenditure. Post-exercise energy expenditure was significantly higher (p = 0.03) following high altitude recovery (139 ± 15 kcal) compared to sea-level recovery (98 ± 11 kcal). Participants reported a lower desire to eat when they recovered in the high altitude environment (p = 0.01), though post-recovery leptin concentrations were similar between the two conditions. Post-exercise exposure to a simulated high altitude environment represents a promising method for increasing daily caloric expenditure and lowering appetite. Given the pilot nature of this study, future research is needed to address the question of high altitude recovery on a larger sample over a longer time period and with robust measures of caloric expenditure.